2019
DOI: 10.1371/journal.pone.0205939
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gastric motility response to human motilin and erythromycin in human motilin receptor-expressing transgenic mice

Abstract: Motilin is a gastrointestinal peptide hormone that stimulates gastrointestinal motility. Motilin is produced primarily in the duodenum and jejunum. Motilin receptors (MTLRs) are G protein-coupled receptors that may represent a clinically useful pharmacological target as they can be activated by erythromycin. The functions of motilin are highly species-dependent and remain poorly understood. As a functional motilin system is absent in rodents such as rats and mice, these species are not commonly used for basic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…Secondly, our current experiment was performed using only EM; motilin was not employed. The basis for this distinction between the effect of EM and motilin in our model is unknown, and contrasts with a report showing that EM and motilin have similar effects on isolated stomach [19]. These results suggest that, in vitro (ex vivo), EM and motilin behave similarly, presumably via direct action on MLNR, but that, in vivo, additional elements affect the response to these drugs.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Secondly, our current experiment was performed using only EM; motilin was not employed. The basis for this distinction between the effect of EM and motilin in our model is unknown, and contrasts with a report showing that EM and motilin have similar effects on isolated stomach [19]. These results suggest that, in vitro (ex vivo), EM and motilin behave similarly, presumably via direct action on MLNR, but that, in vivo, additional elements affect the response to these drugs.…”
Section: Discussioncontrasting
confidence: 93%
“…In contrast, central administration of the motilin receptor agonists can induce effects only via one pathway, through efferent neurons. Our results support those of previous studies [19,26,27,28], which showed how motilide acts and indicated that centrally administered motilides do not infiltrate through the blood-brain-barrier.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As functional motilin system is absent in rodents, these species are not commonly used for translational studies; hence, the expression of the LOF variants nor lessons from knockout mice are limited. Recent studies examine the usefulness of human MTLR -overexpressing transgenic mice that could be used for such follow-up experiments ( 8 ). Moreover, further studies are warranted to explore whether there are other rare LOF loci, leading to or predisposing to gastroparesis, because currently, these rare variants are explaining only a small proportion of patients with gastroparesis.…”
mentioning
confidence: 99%
“…Importantly, a reduction in extracellular [Ca 2+ ] resulted in a synchronous decrease in vasorelaxation, indicating that extracellular Ca 2+ is involved in motilin-induced LGA relaxation. Extracellular Ca 2+ also participates in the motilininduced contraction of SMCs (Kato et al, 2019). However, Ca 2+ enters excitable SMCs and non-excitable ECs mainly via voltage-operated Ca 2+ channels and store-operated Ca 2+ channels (SOCCs), respectively (Tsoukias, 2011).…”
Section: Discussionmentioning
confidence: 99%